2016
DOI: 10.1039/c6ra05942b
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun functionalized polyacrylonitrile–chitosan Bi-layer membranes for water filtration applications

Abstract: Water scarcity has become a global systemic risk, prompting the development of more efficient filtration technologies. Recently, increasing attention has been given to low cost membrane materials such as polyacrylonitrile (PAN) nanofibers for water filtration. In this study, electrospun PAN nanofibrous membranes were functionalized with zinc oxide (ZnO) nanoparticles and coated with a layer of electrospun chitosan (Cs), in order to improve the mechanical properties, and anti-bacterial and water filtration perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 70 publications
1
37
0
Order By: Relevance
“…26,35,38,[41][42][43][46][47][48] In this work, a solution containing 6 wt % of PAN was electrospun leading to highly homogeneous fibrous membranes with D f equals to 400 nm with a diameter distribution from 250 to 750 nm ( Figure 3). 26,35,38,[41][42][43][46][47][48] In this work, a solution containing 6 wt % of PAN was electrospun leading to highly homogeneous fibrous membranes with D f equals to 400 nm with a diameter distribution from 250 to 750 nm ( Figure 3).…”
Section: Fabrication Of Pan-based Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…26,35,38,[41][42][43][46][47][48] In this work, a solution containing 6 wt % of PAN was electrospun leading to highly homogeneous fibrous membranes with D f equals to 400 nm with a diameter distribution from 250 to 750 nm ( Figure 3). 26,35,38,[41][42][43][46][47][48] In this work, a solution containing 6 wt % of PAN was electrospun leading to highly homogeneous fibrous membranes with D f equals to 400 nm with a diameter distribution from 250 to 750 nm ( Figure 3).…”
Section: Fabrication Of Pan-based Fibersmentioning
confidence: 99%
“…[5][6][7][8][9][10] Regarding the inorganic nanoparticles, the scientific community has taken advantage of the photocatalytic activity of zinc oxide (ZnO) to develop materials with antimicrobial activity and dye degradation. 42 Mikal et al also designed PAN/ZnO nanoparticles membranes by electrospinning and explored the effect of fibers composition and test conditions on lead ions removal. More importantly, ZnO is considered as a safe Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of small amounts of metal oxide nanoparticles into electrospun polymeric nanofibers improves their adsorption performance . Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…indicated that the introduction of 4 wt% ZnO nanoparticles into the surface of graphene nanosheets can significantly enhance the adsorption of Ni(II) to a maximum of 66.7 mg/g at room temperature. In a similar study by Makaremi et al ,. the addition of 5 w/w% ZnO nanoparticles into electrospun PAN membranes improved the adsorption efficiency of Cr(III) ions from 4% to 34%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation